Growth and productivity in Australia - Agbenyegah, Benjamin K.; Bloch, Harry (The Economic Society of Australia, 2008)
This paper empirically investigates and identifies the main contributing factors to output and productivity growth in Australia for the period 1950-2005. Cointegration and a vector error-correction model are used along with Granger causality tests, impulse response functions and forecast error variance decomposition analyses to achieve these objectives. Accumulation of human capital and investments in information and communications technology (ICT) are identified as significant in the cointegration analysis of production in Australia and should be included in the long-run production relationship along with fixed capital and labour employed. The vector-error correction model estimates further provide evidence that human capital and ICT are important drivers of output growth in Australia, so their omission from standard productivity measures leads to inaccurate measures and may mislead policy formulation, planning and budgeting decisions.